Satisfaction of clinical learning environment among undergraduate nursing students in Universiti Sains Malaysia - Jalil, Iswaneedawati Abdul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2021)
The quality of clinical learning usually reflects the quality of the curriculum structure. Clinical practice plays a substantial role for better teaching and essential skill in nursing education. This study aimed to evaluate the satisfaction level of the clinical learning environment among nursing students in USM. Besides, this study also investigates the association between socio-demographic data with the total satisfaction level among undergraduate nursing students in USM. This study involves 110 respondents through stratified random sampling. The online questionnaire was used for data collection from February 2021 to March 2021. The mean age of the respondents was 21.15 (1.082) years ranged from 19 years to 23 years old. The findings revealed that majority 87 (79.1%) of students have a high satisfaction level in the clinical learning environment. Three socio-demographic data which are years of study (p = 0.006), type of ward in last clinical placement (p = 0.032) and duration of practical (p = 0.013) have statistically significant difference with total satisfaction of clinical learning environment. In conclusion, the satisfaction level of the clinical learning environment is high but there is still have dissatisfaction shows the need for further enhancement to maximise the satisfaction level of the clinical learning environment among nursing students and for better nursing practise in the future.